The level of Satisfaction among the Teachers in Governmental Schools About The Organizational Climate in Mafraq and Its Relation to The Organizational Loyalty of Teachers in Their Schools - Rqabat, Raed Mohammed Mfdi (Journal of Educational and Psychological Sciences, 2018)
The study aimed at revealing the level of Satisfaction among the Teachers in governmental Schools about the Organizational Climate in Mafraq and Its Relation to The Organizational Loyalty of Teachers in Their Schools. The researcher used the analytical descriptive method in answering the study questions. A random sample was chosen from (312) Public schools in the Directorate of Mafraq Education. In order to achieve the objective of the study, the researcher built two tools for the study, the first consisted of (25) paragraphs, and the second was consisted of (12) paragraphs, and was verified the validity and stability, and the results indicated that the level of satisfaction of teachers in governmental schools about the organizational climate on the tool as a whole was (3.52), the order of the fields was in descending order according to the level of teachers satisfaction: managerial leadership (3.70) organizational structure (3.45), field of work (3.41), performance appraisal (3.38), the field of incentives (3.36). The results showed that there were no statistically significant differences at the level of (α = 0.05) in the level of satisfaction among the teachers of the governmental schools about the organizational climate due to gender variable, years of experience and scientific qualification. Organizational Climate and Organizational loyalty, In the light of the results , a number of recommendations and proposals were presented to increase the satisfaction of teachers and their organizational loyalty in the schools of Mafraq governorate and the whole of the kingdom of Jordan.